Comparative Suitability of RISHA’s Modular Structure for the Spatial Dimension of Human Activities : (Case Study: The Living Bandung Korean Project Building, Indonesia) - Carissa; Maurina, Anastasia; Prastyatama, Budianastas; Wimala, Mia (Journal of Advanced Industrial Technology and Application, 2021)
Rumah Instan Sederhana Sehat (RISHA or the Simple Healthy Instant House) is a prefabricated, modular, and knock-down system for simple housing, developed by the Research Institute for Human Settlements, Ministry of Public Works and Housing in 2004. The current modular grid and its component sizes, which were initially developed based on the type of 36 m2 simple house, produce a space following the required function. The Living Bandung Korean Project (LBKP) building, selected as the case study of RISHA application on a non-residential building in this research, was programmed with multiple functions on its two stories. The study aims to gauge the suitability of RISHA components against each function in LBKP. Started with a literature study, this research focuses on comparing the referenced standard architectural spatial dimension for human activities and functions to that programmed into the LBKP building. The result shows that of the eight analyzed functions, almost all the spatial dimensions using RISHA components do not meet the standard. The RISHA components are too long for functions requiring smaller spaces, such as pantry and toilet, yet too short for ones requiring larger spaces, e.g., workshops, office, musala, minimarket, café, and guest rooms. This result is expected to inform the future development of RISHA’s alternative component sizes to fulfill the space functions. Wimala